Business Strategy Through Acquisition By Developing Selection Process Model on Target Company (Case Study PT Sincerity Investama Abadi, Jakarta, Indonesia) - Reyhan Devtyan Muhammad; Raden Aswin Rahadi; Uke Marius Siahaan (Publikasi Indonesia, 2025)
This study develops a comprehensive selection model framework for acquiring target companies, with a specific focus on PT Sincerity Investama Abadi in Jakarta, Indonesia. The research integrates quantitative valuation methods, including Discounted Cash Flow (DCF) and the Adjusted Net Asset Method (ANAM), with financial ratio analysis to support strategic acquisition decisions. Through the systematic evaluation of five SME candidates using a weighted scoring model, the study identifies the most viable investment opportunities based on financial performance, management readiness, and strategic fit. The findings demonstrate that PT Multindo Cipta Kreasi emerges as the primary acquisition target, with a combined valuation of IDR 2.48 billion and a projected IRR of 15.69%, followed by Omen Futsal as a secondary diversification option. The proposed framework provides private equity and investment firms with a practical tool for optimizing acquisition choices, mitigating risks, and enhancing value creation. The study offers strategic implementation recommendations to improve the selection process and support sustainable investment decisions in the SME sector.